2013
DOI: 10.1080/09593330.2013.855822
|View full text |Cite
|
Sign up to set email alerts
|

Mesophilic anaerobic co-digestion of sewage sludge and orange peel waste

Abstract: Mesophilic anaerobic digestion is a treatment that is widely applied for sewage sludge management but has several disadvantages such as low methane yield, poor biodegradability and nutrient imbalance. In this paper, we propose orange peel waste as an easily biodegradable co-substrate to improve the viability of the process. Sewage sludge and orange peel waste were mixed at a proportion of 70:30 (wet weight), respectively. The stability was maintained within correct parameters throughout the process, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Even after the extraction of limonene prior to AD, studies have shown that inhibition of the AD process occurred, particularly when the organic loading rate (OLR) was increased from 3.67-5.10 gVS l -1 d -1 (Martin et al, 2010;Wikandari et al, 2015). In addition, the co-digestion of orange peel and sewage sludge (70:30) resulted in a methane yield of 0.165 l gVS -1 added and the accumulation of volatile fatty acids when the OLR was above 1.6 gVS l -1 d -1 (Serrano et al, 2014). Likewise, furans (furfural, hydroxymethylfurfural (5-HMF)) are produced during the dehydration of pentose-and hexose-sugars locked within the lignin structure (Barakat et al, 2012).…”
Section: Direct Inhibitionmentioning
confidence: 99%
“…Even after the extraction of limonene prior to AD, studies have shown that inhibition of the AD process occurred, particularly when the organic loading rate (OLR) was increased from 3.67-5.10 gVS l -1 d -1 (Martin et al, 2010;Wikandari et al, 2015). In addition, the co-digestion of orange peel and sewage sludge (70:30) resulted in a methane yield of 0.165 l gVS -1 added and the accumulation of volatile fatty acids when the OLR was above 1.6 gVS l -1 d -1 (Serrano et al, 2014). Likewise, furans (furfural, hydroxymethylfurfural (5-HMF)) are produced during the dehydration of pentose-and hexose-sugars locked within the lignin structure (Barakat et al, 2012).…”
Section: Direct Inhibitionmentioning
confidence: 99%
“…[7] However, it is necessary to determine the possible mixtures and the most important operational variables, such as Y CH 4 /S , organic load rate (OLR) and stability. Gunaseelan [8] studied the anaerobic digestion of fruit and vegetable wastes and observed substantial variations in the methane yield depending on the working temperature (28°C or 35°C), the fruit variety (CH 4 yields of 211 and 384 mL/g VS added were obtained for pyriforme and commune tomato varieties, respectively), and different fruit parts within the same variety.…”
Section: Introductionmentioning
confidence: 99%
“…Co digestion of sludge with other feedstocks such as organic residues as glycerol (Athanasoulia et al 2014), landfill leachates (Pastor et al 2013) agricultural wastes or energy crops (Hidaka et al 2013;Galitskaya et al 2014) or food wastes (Serrano et al 2014;Belhadj et al 2014;Powell et al 2013;Dai et al 2013) would increase the efficiency of the process as well as the quality of the digested liquor and sludge. The economic evaluation of developing a biogas unit within a sewage treatment plant accepting more inflows than sewage to increase the methane potential could be based on the work of Karellas et al (2010).…”
Section: Economic Analysis Of the Pretreatment Methodsmentioning
confidence: 99%